The Effect of Using Inter-Frame Coding with Jpeg to Improve the Compression of Satellite Images - M.Mahdi, Aseel; Loay E.George; G. Mohammed, Faisal (Iraqi Journal of Science, 2021)
Many recent satellite image compression methods depends on removing the spectral and spatial redundancies within image only , such these methods known as intra-frame(image) coding such as predictive and transformed based techniques , but these contributions needs a hard work in order to improve the compression performance also most of them are applied on individual data. The other trend is to exploit the temporal redundancy between the successive satellite images captured for the same area from different views, different sensors, or at different times, which will be much correlated and removing this redundancy will improve the compression performance and this principle known as inter-frame(image) coding .In this paper, a latest powerful method for compressing sequences of satellite images using inter-frame coding concept with compression method (JPEG) has been presented to satisfy higher compression performance while keeping images quality as well as preservation of significant image details. The experimented results show that the proposed method outperformed many of lossy methods including JPEG.